A Facile Carbon Quantum Dot‐Modified Reduction Approach Towards Tunable Sb@CQDs Nanoparticles for High Performance Sodium Storage. Issue 5 (4th February 2020) - Liu, Fei; Wang, Yaping; Zhang, Yifang; Lin, Jiande; Su, Qiong; Shi, Junrong; Xie, Xuefang; Liang, Shuquan; Pan, Anqiang
Abstract: Antimony (Sb) has considerable specific capacity as an anode material for sodium‐ion batteries. However, the large volume expansion during alloying/dealloying with Na + leads to poor cycling stability. Herein, we report the synthesis of Sb@carbon quantum dots (Sb@CQDs) composite via a facile one‐step reduction approach at room temperature. CQDs can modify the nucleation and growth of Sb particles during the reduction process and thus tune the size of Sb. Sb@CQDs particles with size of ∼7 nm can relieve the volume expansion and reduce the diffusion distance for sodium ions. Moreover, the residual CQDs in the obtained composite enhance the electronic conductivity. Benefited from the modification of CQDs, the Sb@CQDs composite delivers high specific capacity of 635 mA h g −1 at 0.1 A g −1 and 334 mA h g −1 at 2 A g −1 . Abstract : Avoiding aggregation : Nanoscale Sb@carbon quantum dots (Sb@CQDs) composite with high sodium diffusion coefficient and optimized electrochemical properties is synthesized via a facile one‐step reduction approach at room temperature. CQDs as functionalized inducers can effectively tune the size and prevent the aggregation of Sb particles. The remarkable electrochemical performances are attributed to the unique structure modified by CQDs, which can enlarge the contact area of electrode and electrolyte, shorten the Na + transfer path, and alleviate the volume changes along cycling.